Blue Growth: Sea Urchin Sustainable Aquaculture, Innovative Approaches - Rubilar, Tamara (2021)
Introduction: “Blue Economy” refers to ocean-based economies with a sustainable approach. It focuses in smaller carbon footprints and efficiency, principles that can be applied to aquaculture. However, it has been difficult to develop successful blue economy projects in sea urchin aquaculture. Objective: To compare URCHINOMICS (Norway) and ARBACIA (Argentina), two aquaculture projects with different business models. Methods: We used publicly available information to compare both companies on the basis of their value proposition and tensions (e.g. cultural, social economic and technological). Results: To be successful, sea urchin aquaculture requires development of appropriate technology, open innovation and cooperation of people with different academic, business and organizational backgrounds. Conclusion: The ultimate success of these and similar companies will depend on free interaction of experts from multiple fields and on technological innovation.